RESISTANCE OF MUSLIMS TOWARD THE GOVERNMENT'S POLICY ON PROHIBITING CONGREGATIONAL WORSHIP DURING THE COVID-19 PANDEMIC - Henky Fernando; Irwan Abdullah; Mohamad Yusuf (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
During the 2020-2021 period in Indonesia, the stricter enforcement of worship practices amid the Covid-19 pandemic resulted in opposition from various Muslim community. Prior research on this phenomenon has solely concentrated on binary notions of opposition, and as such, has not provided a comprehensive explanation of the resistance stance. The objective of this study is to elucidate the shape and manner of resistance from various Muslim groups towards the stricter enforcement of religious practices amid the Covid-19 outbreak. Qualitative methods were employed in this study, which involved collecting data through in-depth interviews and observations conducted at Mataram Mosque in Kota Gede, Yogyakarta. The findings show that resistance by some Muslim communities comes in three forms: passive, active, and reactive resistance. These three forms of opposition represent a manifestation of the citizens' ideological consciousness as they object to government policies that contradict the knowledge and collective experiences they have accumulated thus far.Pada rentang 2020-2021, kebijakan pengetatan pelaksanaan ibadah di masa Covid-19 di Indonesia telah menimbulkan sejumlah resistensi dari beberapa segmen masyarakat muslim. Studi terdahulu yang membahas fenomena ini hanya terfokus pada konsep resistensi yang dikotomis, sehingga belum menjelaskan sikap resistensi secara komprehensif. Penelitian ini bertujuan untuk menjelaskan bentuk dan pola resistensi beberapa segmen masyarakat Muslim terhadap kebijakan pengetatan kegiatan ibadah di masa pandemi Covid-19. Penelitian dilakukan melalui metode kualitatif dengan teknik pengumpulan data berupa wawancara mendalam dan observasi di Masjid Mataram Kota Gede, Yogyakarta. Temuan menunjukkan bahwa perlawanan yang dilakukan oleh sebagian masyarakat Muslim tersebut muncul dalam tiga bentuk, yaitu: perlawanan secara pasif, aktif, dan reaktif. Ketiga bentuk resistensi tersebut merupakan wujud kesadaran ideologis warga karena ketidaksetujuan terhadap kebijakan pemerintah yang berseberangan dengan pengetahuan dan pengalaman kolektif yang mereka miliki selama ini.